Identifying the Practical Application Opportunities of Architectural Design through a Creative Approach (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the theoretical foundations of a creative approach in the field of architectural design, its application possibilities in the educational process and practice, as well as its effectiveness factors. The concept of creativity is explained based on scientific sources, highlighting its role in developing students’ independent thinking, creative decision-making, and professional competencies. In addition, the article demonstrates the practical importance of a creative approach in urban planning, landscape design, interior design, and the integration of national heritage. The results of the study confirm that classes organized on the basis of a creative approach ensure high efficiency in improving students’ professional skills.